Influential factors in the competitiveness of mature tourism destinations - Santos, Margarida Custódio (2014)
73 Tourism & Management Studies, 10(1) 2014 Influential factors in the competitiveness of mature tourism destinations Os fatores que influenciam a competitividade dos destinos turísticos maduros Margarida Custódio Santos University of the Algarve, School of Management, Hospitality and Tourism, Campus da Penha, 35, 8005-139, Faro, Portugal, mmsantos@ualg.pt Ana Maria Ferreira University of Évora, Department of Sociology, 7004-516, Évora, Portugal, amferreira@uevora.pt Carlos Costa University of Aveiro, Department of Economics, Management and Industrial Engineering, GOVCOPP, 3810-193, Aveiro, Portugal, ccosta@ua.pt Abstract With a few exceptions, the traditional models that aim at identifying the factors that influence the competitiveness of tourism destinations are very difficult to operationalise because they need a large number of indicators to inform the concepts. This paper presents a different approach that postulates that researchers should try to identify the specific factors that impact competitiveness of tourism destinations according to the stage of the destinations’ life cycle. With the aim of identifying these specific factors, an extensive literature review was undertaken, focusing in particular on the papers that explicitly recognised that the destinations under analysis in the studies were in the mature stage of their lifecycle. From the literature review, we concluded that the specific factors able to negatively influence the performance of mature tourism destinations can be grouped into four areas. The first area concerns the deterioration of the destinations’ infrastructure; the second is related to the destinations’ management, namely the lack of a shared strategic vision among stakeholders; the third area is associated with the loss of economic vitality in the destinations; finally, the fourth area includes the impact of tourism development over the years on the territory, specifically social, environmental and cultural impacts. The results obtained from the empirical study allow us to conclude that the lack of environmental problems, not being overdeveloped in terms of construction and having maintained authenticity are all perceived by tourists as more important for the competitiveness of tourism destinations than factors normally considered more relevant, such as prices and the quality of accommodations.